Application of Bibliometrix Software and Scientific Review in Technology and Education Field - Jiménez-Martínez, Carmelo; Núñez-Cansado, Marian; Martín Moraleda, Ignacio José (Street Art & Urban Creativity, 2025)
Technological competences are related to various thematic lines of impact for students, teachers, and professionals. The growing interest in recent years and the demand of the educational society, leads to the need to evaluate the research process that draws a map of the published scientific literature. The research focuses on a systematic bibliometric analysis, which generates a state of the art of the topic: ‘Technology, education and teaching’. A methodology has been developed based on the Bibliometrix tool for R language, with the IDE R-Studio development interface, completed with an analysis process through the BiblioShinny web environment. The corpus extracted from Web of Science (subject: Social Sciences) in a time frame from 1980 to 2023 is 1889 scientific articles. The results provide a comprehensive mapping of notable authors, relevant journals, changes in thematic trends, and the social structure of inter-university and international collaborations.